2011
DOI: 10.1016/j.maturitas.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life in ageing populations: What can volunteering do?

Abstract: The year 2011 was declared the 'European Year of Volunteering' to recognise the contribution volunteers make to society. Such cross-national events reflect the high profile of volunteering and political imperatives to promote it. The purpose of this review is to provide a comprehensive review of current knowledge (articles published between 2005 and 2011) regarding the role of volunteering in improving older people's quality of life (QoL) and to identify areas requiring further research. Volunteering was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 30 publications
5
74
0
1
Order By: Relevance
“…Studies in USA [15] reveal that older people participating in voluntary work "predicted better self-rated health, functioning, physical activity and life satisfaction as well as decreased depression and mortality". Several studies analyzed in the literature review conducted by Cattan, Hardill and Hogg [24] point to the positive effect of volunteering, in reducing the risk of depression and decreased depressive symptoms in the elderly. Indeed, it was found that there was a reduction in the level of loneliness in elderly volunteers, higher than the remaining senior citizens.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Studies in USA [15] reveal that older people participating in voluntary work "predicted better self-rated health, functioning, physical activity and life satisfaction as well as decreased depression and mortality". Several studies analyzed in the literature review conducted by Cattan, Hardill and Hogg [24] point to the positive effect of volunteering, in reducing the risk of depression and decreased depressive symptoms in the elderly. Indeed, it was found that there was a reduction in the level of loneliness in elderly volunteers, higher than the remaining senior citizens.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…more favorable) scores on the 11-item version of the Center for Epidemiologic Studies Depression (CES-D) scale. Other researchers have found that volunteering is associated with increased life satisfaction [14] and quality of life [15]. Tan et al [18], in adjusted analyses of 113 volunteers who were randomized into either the Baltimore Experience Corps condition or a waiting list control condition, found that although Experience Corps volunteers reported increased physical activity at 8 months post-randomization compared to those in the control group, the difference was not significant (p = 0.49).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, prosocial behavior has been associated with positive outcomes in the problem solving and drug dependence literature, particularly among adolescents [10]. Volunteerism, a form of prosocial behavior, has also been associated with positive outcomes among older adults [1115]. Of note, the Baltimore Experience Corps Program [16], which places predominately older African-American volunteers in public elementary schools [17], is designed to improve academic outcomes of children and physical activity, cognitive and social outcomes of volunteers [18].…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Berg, O. Johansen worth and socialization [17], as well as higher levels of self-rated life satisfaction [18]. Older adult volunteers have reported an increase in their quality of life due to feeling appreciated, having a sense of purpose, and being able to "give something back" [19].…”
Section: Literature Reviewmentioning
confidence: 99%